Effect of ethanol extracted propolis (EEP) on growth performance in the meat type Japanese quails - Kadhim, Mohammed Jard (Journal of Kerbala for Agricultural Sciences, 2019)
The objectives of this experiment were to evaluate the performance of two varieties of sunflower (Helianthus annuus L.) with three plant densities (40, 50 and 60 thousands of plants.ha-1.) and estimate the phenotypic, genotypic and environment variation, phenotypic and genotypic coefficient of variation, heritability, stability and genetic resultant, for two seasons. The experiments were conducted during spring and fall seasons of 2013, using factorial experiment within RCBD with four replicates. The results showed the superiority of Shimoos variety, it gives seed yield 3.345 t.ha-1 compared with Aqmar variety which gave 2.375 t.ha-1 in spring season, at fall season Shimoos variety gave 6.265 t.ha-1, while Aqmar variety gave 5.379 t.ha-1. The yield increased with plant density increasing, it ranged from 2.425 to 3.222t.ha-1 in spring season and from 4.396 to 5.822t.ha-1 in fall season. The values of phenotypic stability were different according to differences between varieties and seasons. The high value was 93.75% for disc area followed by 90.13% for seed yield t.ha-1 for Aqmar in spring season and the higher value for Shimoos variety was 94.15 for disc area followed by 90.66% and 90.55% for 100 seed weight and number of seeds in disc respectively. . All values of genetic variation are higher than environment variation, and were closed to phenotypic variations for spring and fall seasons, except for seed number in disc in fall season which was less than environment variation. Hence the heritability for these traits were high and ranges from 63% for seed number in disc to 95% for shoot dry weight in spring season and from 33% for seed number in disc to 99.6% for disc area in fall season. So the genetic coefficient of variation for all traits is closed to phenotypic coefficient variation. The traits: plant growth rate and shoot dry weight for Aqmar, and leaf area index, plant growth rate and seeds yield for Shimoos showed non phenotypic stability in spring season. In fall season, seed yield t.ha-1 for Aqmar was the only trait non-phenotypic stable. The genetic results are ranged from 65.32% for shoot dry weight to 98.86% for seed number in disc for Aqmar and from 81.34% for seed number in disc to 114.79% for 100 seed weight for Shimoos in spring. In fall season, it ranges from 69.18 for leaf area index to 96.02% for seed number in disc for Aqmar and from 89.25% for seed number in disc to 107.32% for disc area for ShimoosIt is possible to conclude that Shimoos variety was superior in most of the traits. So we recommend planting Shimoos variety in the fall season, because it is more stable than Aqmar variety, while Aqmar variety can be cultivated in the spring season.